Analisis Pertumbuhan Kinerja Keuangan PT. Bank Mandiri Persero (Tbk) - Tuti Hermelinda (Jurnal Ilmiah Raflesia Akuntansi, 2019)
This research was made with a view to assess and analyze financial performance of PT Bank MandiriTbk. The assessment was conducted by looking at the financial ratios of from 2013 until 2017, from the financial statements obtained from the website of Indonesian stock exchange, the value of the components of financial statements conducted re-calculation formula into the valuation ratios of the banking financial performance, then the results of are analysed per year. Conclusions from this analysis is compared with indicators of banking health assessment released by Bank Indonesia. Analysed financial ratios taken are among others ROA, ROE, NIM, BOPO, LFR . These are commonly used ratios by researchers in assessing the financial performance of banks.